Giant Choledochal Cyst Mimicking Massive Gallbladder Hydrops in an Adult Patient: Multi Detector Computed Tomography and Magnetic Resonance Imaging Findings Correlated to Gross and Histopathological Findings - Choi, Joon-Il (Medknow Publications & Media Pvt Ltd, 2013)
Choledochal cysts are uncommon congenital anomalies of the biliary tree, commonly presenting in infancy, generally in the 1(st) year of life. Presentation in adult life is less common, accounting for 20% of cases. A 19-year-old female patient presented to the Emergency Department with severe abdominal distension, a palpable abdominal mass, mild jaundice and low grade fever. Ultrasound, computed tomography (CT) and magnetic resonance imaging of the abdomen showed a massive septated cystic lesion filling the entire abdomen with a significant mass effect on surrounding structures. Origin of the lesion was unclear and diagnosis included a giant mesenteric or duplication cyst, massive gallbladder with hydrops, biliary cystadenoma and giant choledochal cyst, among others. Final diagnosis was a Type IA choledochal cyst with massive asymmetric cystic dilatation of the extra-hepatic segments of the left hepatic duct with asymmetric dilatation of the right hepatic duct. Patient had an uneventful recovery after resection of the entire extrahepatic cyst and Roux-en-Y hepaticojejunostomy at the level of the hilum. In this article, we correlate CT and MRI findings to gross and histopathological findings of this giant Todani's Type IA choledochal cyst.